Between Wittenberg and Geneva : Lutheran and Reformed theology in conversation - Kolb, Robert, 1941-; Trueman, Carl R. (Grand Rapids, MI Baker Academic, 2017)
At the 500th anniversary of the Wittenberg Reformation, two highly regarded scholars compare and contrast the history and theological positions of the Reformed and Lutheran traditions. The authors tackle nine theological topics significant for the life of the church that remain a source of division between the two traditions. The book helps readers evaluate the strengths and weaknesses of the Reformed and Lutheran approaches to presenting the biblical message and invites honest, irenic, and open dialogue within the Protestant family.
Scripture and its interpretation -- Law and Gospel -- The person and work of Christ -- Election and the bondage of the will -- Justification and sanctification -- Baptism -- The Lord's Supper -- Worship.
Includes bibliographical references and indexes.
Keywords: Luther, Martin, -- 1483-1546.; Lutheran Church -- Doctrines; Reformed Church -- Doctrines